Research And Application of The "5-Target Customer Analysis Model" to Address The Illegal Wildlife Trade: The Case of The United States Fish and Wildlife Service - Cheng, Yu (Transactions on Economics, Business and Management Research, 2024)
Against the backdrop of the illegal wildlife trade being a global problem involving many governmental and non-governmental organisations, this paper proposes a "5-goal client analysis model" to address this challenge. Firstly, five key assessment indicators, including enforcement capacity, financial support level, human resource level, technological innovation and international co-operation experience, were selected to identify relevant entities to deal with illegal wildlife trade. Potential clients were assessed and analysed through the entropy weighted TOPSIS method, combining the concept of information entropy and a comprehensive assessment of multiple aspects of the clientele, which ultimately identified national-level wildlife management agencies as the best users. For the United States as a major wildlife importer and exporter, the U.S. Fish and Wildlife Service (USFWS) was selected as a potential target. The scope of responsibilities, scope of international cooperation, international relations, and wildlife conservation achievements of the USFWS are further presented, showing significant progress and contributions in combating illegal wildlife trade. The model provides a systematic assessment and solution to effectively address the problem of illegal wildlife trade.